PEMILIHAN JENIS POHON MENJERAP DEBU DI MEDIAN JALAN KOTA BANDAR LAMPUNG - Suci Rahmadhani; Slamet Budi Yuwono; Agus Setiawan; Irwan Sukri Banuwa (Jurnal Belantara, 2019)
Trees species are suitable to be planted in the median of the road must be able to absorb and to reduce air pollution. Determination of leaf samples was carried out using the purposive sampling method. The measurement of dust was carried out using a laboratory experimental method, namely the gravimetric method. The results of the research show that the trees that have the greatest dust absorption ability on tanjung (Mimusops elengi) are 0.00123 gr/cm2 and trees that have the ability to lie falsely with mahogany (Swietenia mahagoni) are 0.00022 gr/cm2. Tanjung tree is a plant that has a high ability to absorb dust, has smooth, shiny leaves, curved leaves and curved upward, and fragrant flowers. Tanjung tree is the most effective tree planted in the median road for dust absorption. Tanjung trees are recommended to be planted in the median road so that dust in the air is reduced.